2021
DOI: 10.1186/s42269-021-00518-w
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Malachite green dye by Stenotrophomonas maltophilia a compost bacterium

Abstract: Background The release of triphenylmethane dyes, like malachite green (MG) and crystal violet (CV), into the environment is a cause of concern due to its toxicity, mutagenicity and carcinogenicity. Result A bacterial strain that is capable of decolorizing both dyes was isolated from the composted neem oil-seed cake. The strain was characterized as Stenotrophomonas maltophilia based on the 16S rRNA gene sequence and designated as isolate TPMD-1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…The samples of culture tubes were centrifuged at 5000 rpm for 20 min. The remaining concentration in the aliquots were determined through UV-Visible spectrophotometer [16].…”
Section: The Impact Of Ph On Dye Degradationmentioning
confidence: 99%
“…The samples of culture tubes were centrifuged at 5000 rpm for 20 min. The remaining concentration in the aliquots were determined through UV-Visible spectrophotometer [16].…”
Section: The Impact Of Ph On Dye Degradationmentioning
confidence: 99%
“…Cheng et al also reported that bioremoval of RB5 was performed by O. anthropi with the highest efficiency at pH 7 and 9 19 . Alaya et al reported that S. maltophilia had an efficient malachite green removal yield at pH 8 21 . Johansson et al concluded that pollutant reduction efficiency was dye‐specific and pH‐dependent due to dye‐enzyme interactions 22 .…”
Section: Resultsmentioning
confidence: 99%
“…19 Alaya et al reported that S. maltophilia had an efficient malachite green removal yield at pH 8. 21 Johansson et al concluded that pollutant reduction efficiency was dye-specific and pH-dependent due to dye-enzyme interactions. 22 In this study, the highest Setazol Black B removal rate was achieved at pH 8, likely due to the pH-dependent nature of dye-enzyme interactions.…”
Section: Effect Of Ph On Bioremediation By Bacterial Consortiummentioning
confidence: 99%
“…We believe that the present study is one of the few reports that deal with the screening of bacterial laccases as far as our knowledge. As a result of a literature survey, it was shown that some S. maltophilia E1 strains had been implicated in the production of laccase (Galai et al 2009 ; Alaya et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%